Development of Student Worksheets (LKPD) Based on Contextual Teaching and Learning (CTL) on the Subject of the Association - Arisa, Resti (Lembaga Riset Mutiara Akbar, 2022)
The problems found in this study were regarding the Contextual Teaching and Learning (CTL)-based Student Worksheets teaching materials which still rarely used set material. Besides that, there are also several CTL-based LKPDs on the set material that are less able to help students relate the material studied to real everyday life, the questions presented in the LKPD are also still not simple, making it difficult for students to understand the material. So from this problem, a problem formulation emerged, namely how to develop CTL-based LKPD on the subject of the set, is the CTL-based LKPD on the set material suitable for use as a learning medium? and how do students respond to CTL-based LKPD on set material? The purpose of this study was to determine whether the CTL-based LKPD on the set material was appropriate or not and to find out the students' responses to the developed LKPD. This type of research is a type of research and development (Research and Development or R & D) which is modified into 3-D. The subjects of this study were lecturers and teachers of mathematics as validation of material and media experts and 10 students of PAB 3 Saentis Private Junior High School. The object of this research is to develop student worksheets based on contextual teaching and learning on the subject of the set. The research instrument is the LKPD questionnaire for expert validation and student responses. Validity results can be obtained through the assessment of material experts, media experts and students. Based on the calculation of the average percentage of assessment experts given by material experts is 82.9% and the assessment given by media experts is 83.7% and the results of the assessment of student responses are 89.85%. So it can be concluded that the LKPD based on contextual teaching and learning on the subject of the set is declared valid and feasible to be used as a learning medium because it has met the validity requirements in the table used.